Germination of the seeds of Gleditsia triacanthos L. and the effect of some agricultural communities on the growth and development of their seedlings - redwan, Osama (Latakia University Journal -Biological Sciences Series, 2019)
The study was conducted during the years 2016 - 2017 in order to study the appropriate methods and conditions for the production Gleditsia triacanthos plantings through sexual propagation. The study focused on trying to obtain the best rate of germination of the seeds of the Gleditsia triacanthos and the search for the best substrate for the growth of its seedlings and thus get the plantings with a quality required for afforestation. The study found that The 48-hour soaking treatment achieved the best percentage of germination and the highest percentage of germination was found in the turf substrate and was significantly superior to the rest of the agricultural substrates used, and gave the best values ​​for the shoot and root systems of the developing Gleditsia seedlings ., and the positive effect of turf substrate improved the values ​​of measured indicators during its mixing with forest nursery soil. Thus, it is possible to modify the values ​​of the nursery soil through the mixing process with the turf. أجريت الدراسة خلال العامين 2016 - 2017 بهدف دراسة الطرائق والظروف المناسبة لإنتاج غراس الغلاديشيا ثلاثية الاشواك عن طريق الإكثار الجنسي. ركزت الدراسة على محاولة الحصول على أفضل نسبة لإنبات بذور الغلاديشيا والبحث عن أفضل وسط زراعي لنمو بادراته والحصول بالتالي على غراس تمتاز بالجودة المطلوبة لأعمال التشجير. بينت الدراسة أن معاملة النقع لمدة 48 ساعة حققت النسبة المئوية الأفضل في الإنبات وخلصت الدراسة إلى ان أعلى نسبة انبات كانت في وسط التورف وتفوق معنوياً على باقي الأوساط الزراعية المستخدمة, وأعطى أفضل القيم الخاصة بالمجموعين الخضري والجذري لبادرات الغلاديشيا النامية. كما ظهر التأثير الإيجابي للتورف في تحسين قيم المؤشرات المقاسة أثناء عملية خلطه مع تربة المشتل الحراجي. وبالتالي إمكانيّة تعديل القيم الخاصة بوسط تربة المشتل من خلال عملية الخلط مع التورف.